European Traders In Regional Trade Of Malay Archipelago, 1681-1792 [HC445.5. Y46 2007 f rb]. - Yeoh, Lian Heoh (2007)
This study of economic history covers the period between1681 – 1792 and is confined to Melaka and other ports in the Malay Archipelago.